Powiązania kursu walutowego i wymiany handlowej Polski: Relationship between exchange rate and Polish trade - Przekota, Grzegorz; Lisowska, Agnieszka (Management and Administration Journal, 2021)
The study relate the relationship between the exchange rate and the level of Polish trade. Analyzed monthly data for the period January 2000 - December 2011. The research found that the relationship between the exchange rate and the level of trade is not based on a simple correlation. However, it was found that in the formation of trade is the dominant role of the dollar over the euro. In addition, causality the trade - the exchange rate is bilateral.